Impacto da galectina-3 no curso da infecção experimental por Trypanosoma cruzi - Silva, Aline Alves da (2015)
Galectin-3 (Gal-3) is a protein of the lectin-family, has affinity for β-galactose-containing carbohydrates, and can be localized in nucleus, cytoplasm, membrane associated or secreted. This protein is involved in many immunoregulatory processes, such as DC/T lymphocyte adhesion, inflammatory responses and cell migration toward inflammatory foci and cell proliferation. It was also seen that the T. cruzi infection, that is the etiological agent of Chagas disease, increases the expression of Gal-3. Thus, in this paper we aim to explore the biological activities of galectin-3 in acute and chronic T. cruzi experimental infection. Mice C57/BL6 Wild-Type (WT) and galectin-3 knockout (Gal-3KO) were infected intraperitoneally and was evaluate parasitaemia, recruitment of inflammatory cells in the peritoneal cavity, production of cytokines in spleen and heart and cardiac fibrosis. The data presented here demonstrate that the lack of Galectin-3 enhanced the parasitaemia and reduced the recruitment of leukocytes. In heart samples, we observed an increased secretion of TNF-α and IFN-γ in WT while in galectin-3 knockout mice we detected increased production of IL-1β and IL-4 during the acute phase. This scenario may have accounted to the higher infection rate during acute infection observed in knockout mice. We observed that in the chronic phase of infection the heart tissue of WT mice showed an immune response to Th2 profile, important to control tissue damage, with basal levels of IFN-γ and TNF-α, decrease in the concentration of IL-1β and increased IL-4. The increase in IL-4 is important for reducing heart damage and was not observed in animals Gal-3 KO. In chronic phase we observed an increased recruitment of mastocyte in Gal-3 KO animals and larger fibrosis of the heart. Therefore, the Gal-3 showed chemotactic and immunoregulatory functions that are needed to control the acute phase of infection and decreased chronic heart damage.